LES RÉACTIONS LOCALES LIÉES AU VACCIN BCG - Belamalem Souad; Tebaa Amina; Ouled Errkhis Rachida; Nekkal Nasma; Benkirane Rajae; Khadmaoui Abderrazzak; Mokhtari Abdelrhani; Soulaymani Abdelmajid; Soulaymani Bencheik Rachida (European Scientific Journal, ESJ, 2013)
To evaluate the frequency and severity of associated local reactions to BCG a retrospective study was conducted on the notified in Moroccan Centre Anti Poison and Pharmacovigilance. During this period, 295 cases have been reported following vaccination with BCG local natureMales were the most concerned with 57%. Infants are much more represented (61%) than other age groups. The most local reactions are observed: becegites (37%), abscesses (20%), rash (16%), ulcers (15%), and fistula (12%). Accompanying signs of these local reactions are usually represented by a fever (6%) and lymphadenopathy (2%). BCG was injected intradermally in 87% of cases, followed by the intramuscular route (8%) and the subcutaneous route in 5% of cases. According to the classification of severity of the WHO ART, these reactions were severe in 18% of cases, moderate in 69% and severe in 14% of cases. The relation of cause and effect between BCG vaccination and the occurrence of local reactions is well established with 46% of probable cases and 7% of cases while some is possible in 46%, and excluded in 1%. The outcome was favorable in 85%, 14% recovered with sequelae and 1% was fatal.